Chemical defense in developmental stages and adult of the sea star Echinaster (Othilia) brasiliensis - Pereira, Renato Crespo; Sudatti, Daniela Bueno; Moreira, Thaise S.G.; Ventura, Carlos Renato R. (PeerJ, 2021)
To date, evidence regarding the performance of secondary metabolites from larval stages of sea stars as an anti-predation defense relates only to a few species/specimens from a few geographic ranges. Unfortunately, this hinders a comprehensive global understanding of this inter-specific predator-prey interaction. Here, we present laboratory experimental evidence of chemical defense action in the early developmental stages and adults of the sea star Echinaster (Othilia) brasiliensis from Brazil against sympatric and allopatric invertebrate consumers. Blastulae, early and late brachiolarias of E. (O.) brasiliensis were not consumed by the sympatric and allopatric crabs Mithraculus forceps. Blastulae were also avoided by the sympatric and allopatric individuals of the anemone Anemonia sargassensis, but not the larval stages. Extracts from embryos (blastula) and brachiolarias of E. (O.) brasiliensis from one sampled population (João Fernandes beach) significantly inhibited the consumption by sympatric M. forceps, but not by allopatric crabs and A. sargassensi anemone. In this same site, extracts from adults E. (O.) brasiliensis significantly inhibited the consumption by sympatric and allopatric specimens of the crab in a range of concentrations. Whereas equivalent extract concentrations of E. (O.) brasiliensis from other population (Itaipu beach)inhibited the predation by allopatric M. forceps, while sympatric individuals of this crab avoided the only the higher level tested. Then, early stages and adult specimens of E. (O.) brasiliensis can be chemically defended against consumers, but this action is quite variable, depending on the type (anemone or crab) and the origin of the consumer (sympatric or allopatric).
Keywords: Marine chemical ecology; Tropical region; Echinoderm; Starfish; Sympatric; Allopatric; Echinodermata; Feeding ecology; Anti-predation defense; Predation